A novel 1, 8-naphthalimide derivative with an open space for an anion: unique fluorescence behaviour depending on the binding anion's electrophilic properties1. Issue 41 (21st May 2015) - Izawa, Hironori; Nishino, Shoji; Sumita, Masato; Akamatsu, Masaaki; Morihashi, Kenji; Ifuku, Shinsuke; Morimoto, Minoru; Saimoto, Hiroyuki
<x xml:space="preserve">Abstract</x> We have designed a novel 1, 8-naphthalimide derivative with an open space for an anion.